2013
DOI: 10.1021/es402775z
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Removal from Wastewater by Coupling Anammox and Methane-Dependent Denitrification in a Membrane Biofilm Reactor

Abstract: This work demonstrates, for the first time, the feasibility of nitrogen removal by using the synergy of anammox and denitrifying anaerobic methane oxidation (DAMO) microorganisms in a membrane biofilm reactor (MBfR). The reactor was fed with synthetic wastewater containing nitrate and ammonium. Methane was delivered from the interior of hollow fibres in the MBfR to the biofilm that grew on the fiber's outer wall. After 24 months of operation, the system achieved a nitrate and an ammonium removal rate of about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
145
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(152 citation statements)
references
References 35 publications
7
145
0
Order By: Relevance
“…The results of the long-term experiments also showed that the n-damo bacteria performed better at 35 C than at 30 C. Hitherto n-damo culture was most enriched at 22e30 C Raghoebarsing et al, 2006;Shi et al, 2013), but 35 C might be a better temperature of n-damo bacterial incubation according to this work. Although n-damo bacteria are still active at 45 C with a specific activity of 0.54 ± 0.05 mmol NO À 2 h À1 g À1 VSS, Hu et al (2009) failed to obtain n-damo biomass at 45 C, probably because one or more essential cell components, such as a key enzyme, became so damaged at a high temperature of 45 C that the cells lost the ability of growth (Madigan et al, 2010).…”
Section: Effect Of Temperature On N-damo Processsupporting
confidence: 56%
See 2 more Smart Citations
“…The results of the long-term experiments also showed that the n-damo bacteria performed better at 35 C than at 30 C. Hitherto n-damo culture was most enriched at 22e30 C Raghoebarsing et al, 2006;Shi et al, 2013), but 35 C might be a better temperature of n-damo bacterial incubation according to this work. Although n-damo bacteria are still active at 45 C with a specific activity of 0.54 ± 0.05 mmol NO À 2 h À1 g À1 VSS, Hu et al (2009) failed to obtain n-damo biomass at 45 C, probably because one or more essential cell components, such as a key enzyme, became so damaged at a high temperature of 45 C that the cells lost the ability of growth (Madigan et al, 2010).…”
Section: Effect Of Temperature On N-damo Processsupporting
confidence: 56%
“…A previous work of pH effect on n-damo enrichment culture had been carried out by Zhu et al (2012), but they only investigated a narrow pH range of 5.9e7.4 in which the n-damo activity increased continuously and optimum pH value wasn't obtained, while this work supplied complete information (pH 6.0e9.0) including the part of activity decrease at high pH values. Previous n-damo cultures were most incubated in a pH range of 6.8e7.6 (Ettwig et al, 2009;Luesken et al, 2011;Shi et al, 2013), and the results of this work suggested pH around 7.6 was better than 7.0. In addition, the different pH (7.0 and 7.6) didn't change the percentage of n-damo activity (Table 1) and the abundance of 16S rRNA genes (Table 2), probably because of the similar effect of pH on n-damo and heterotrophic denitrification.…”
Section: Effect Of Ph On N-damo Processmentioning
confidence: 79%
See 1 more Smart Citation
“…Both the anammox bacteria and n-damo bacteria use the same electron acceptor (nitrite), thus they can potentially compete for nitrite in nature. So far, the co-existence of anammox bacteria and n-damo bacteria has been reported in several enrichment cultures (Luesken et al, 2011a;Haroon et al, 2013;Shi et al, 2013;Ding et al, 2014). It was observed that if ammonium was supplied in excess, n-damo bacteria were outcompeted from the enrichment culture, suggesting that anammox bacteria have a higher affinity for nitrite (Luesken et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional nitrification/denitrification process, Anammox does not need external carbon sources, and the power consumption for Anammox can be reduced substantially (Shi, et al, 2013). Therefore, it can effectively treat mature landfill leachate (Anfruns, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%